Mechanical performance of sustainable ternary blended self compacting concrete with waste crushed glass. (2022) - Shiva Srikanth, K.; Lalitha, G.
Abstract: This experimental study was focused on mechanical properties of self-compacting concrete partial substitution of sand with waste glass. SCC is prepared with fly-ash (15%), Alccofine (20%), Cement (65%) by weight of binder material. These proportions are fixed for all the mixes. Waste crushed glass has enough amount of amorphous silica content which is easily replaced by fine aggregate in self-consolidating concrete. The Proportions taken for the replacement of the waste crushed glass are 0%, 10%, 20%, 30% and 40%. Grade of concrete taken was M70 and W/C 0.3 and the fresh properties studied for all concrete mixes. Cube Specimens for strength in compression (100 mm × 100 mm × 100 mm), Cylinders specimens in split tensile (100 mm × 200 mm) casted and tested at 7, 28, 90 days, Flexural beam size (700 mm × 150 mm × 150 mm) are casted to know the flexural behaviour at 28, 90 days. Beams are designed as under reinforced sections. The results are compared with self-compacting control mix and replacement of natural sand using waste crushed glass. The results shown increasing crushed glass content increasing workability of concrete and strength up to 30% of substitution of glass.